ENTANGLEMENT BETWEEN TWO SINGLE-PHOTON SOURCES DUE TO A BEAM SPLITTER - López-Carreño, Juan C; Vinck-Posada, Herbert (MOMENTO, 2014)
We consider a quantum dot of frequency w_s embedded in a semiconductor microcavity interacting with an electromagnetic mode of frequency w_a. The cavity is subject to a pumping laser of power W and frequency w_L, and to dissipative mechanisms such as photonic and excitonic relaxation, at rates g_a and g_s, respectively. The power and frequency of the laser is set so that the cavity-dot system reaches a stationary state, in which it emits single photons. Taking two of this single-photon emitters as the input for a semi transparent beam splitter, we consider the entanglement of the two output states in the low excitation regime using the Peres criteria. Thus, we study the dependence of the entanglement with the photonic and excitonic relaxation rates.